The beauty of resolution: The SN Ib factory NGC 2770 spatially resolved. Issue Volume 10:Issue S309(2014) (9th February 2015) - Thöne, C. C.; Christensen, L.; Gorosabel, J.; de Ugarte Postigo, A.
Abstract: The late-type spiral NGC 2770 hosted 3 Type Ib supernovae (SNe) in or next to star-forming regions in its outer spiral arms. We study the properties of the SN sites and the galaxy at different spatial resolutions to infer propeties of the SN progenitors and the SF history of the galaxy. Several 3D techniques are used and, for the first time, we present images of metallicity, shocks and stellar population ages from OSIRIS/GTC imaging with tunable narrowband filters.